2010
DOI: 10.1007/s12034-010-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled flower-like nanostructures of InN and GaN grown by plasma-assisted molecular beam epitaxy

Abstract: Nanosized hexagonal InN flower-like structures were fabricated by droplet epitaxy on GaN/ Si(111) and GaN flower-like nanostructure fabricated directly on Si(111) substrate using radio frequency plasma-assisted molecular beam epitaxy. Powder X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to study the crystallinity and morphology of the nanostructures. Moreover, X-ray photoelectron spectroscopy (XPS) and photoluminescence (PL) were used to investigate the chemical compositions and opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A nanostructured surface can be obtained either by the direct growth of nanostructures, that is, by chemical vapor deposition, physical vapor deposition (PVD) including sputtering/evaporation/epitaxial growth method, etc., or via engineering the flat surfaces to develop nanostructures using wet/dry etching processes. Kumar et al proposed the growth of InN- and GaN-based self-assembled flower-shaped nanostructures via molecular beam epitaxy (MBE), while Aggarwal et al reported nanoflower decoration on GaN surfaces to enhance light absorption in the fabricated UV PDs. However, compared to growth-related challenges, surface engineering is a simple and convenient approach to develop ordered nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…A nanostructured surface can be obtained either by the direct growth of nanostructures, that is, by chemical vapor deposition, physical vapor deposition (PVD) including sputtering/evaporation/epitaxial growth method, etc., or via engineering the flat surfaces to develop nanostructures using wet/dry etching processes. Kumar et al proposed the growth of InN- and GaN-based self-assembled flower-shaped nanostructures via molecular beam epitaxy (MBE), while Aggarwal et al reported nanoflower decoration on GaN surfaces to enhance light absorption in the fabricated UV PDs. However, compared to growth-related challenges, surface engineering is a simple and convenient approach to develop ordered nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…These peak positions clearly differ from N1s in GaN ͑397.3 and 397.8 eV͒ 11 and InN ͑396.5 eV͒. 12 This indicates that the nitrogen species in the a-IGZO:N thin film has an electronic state similar to the one in Zn 3 N 2 . In order to investigate the uniformity of device characteristics, five different measuring points were sampled for each specimen.…”
mentioning
confidence: 91%